Biological sex estimation using ancient DNA in Classic Maya contexts: some findings from Naachtun (Guatemala) - Hemmamuthé Goudiaby; Xavier Roca-Rada; Kalina Kassdjikova; Lars Fehren-Schmitz; Bastien Llamas (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Recent advances in paleogenomics have opened up new prospects for the study of ancient burial customs and social structures. In this note, we report on the first results of a program now under way in a small residential compound in Naachtun, Guatemala (numbered 5N6). From the burials discovered on the site, a pilot group of seven individuals was selected for DNA analysis. The ancient DNA analysed showed that female individuals are predominant among the dead in this small group, thus highlighting its potential for genetic sexing as well as the reliability of osteological methods for sex estimation. These results outline new horizons for the discipline.